Effect of Performance of A DC Motor by Replacing Ferrite Magnet with Melt Spun NdFeB Magnet - Muhammad Ikhbar B. Md Ismail, Muhammad Ikhbar (Universiti Teknologi PETRONAS, 2008)
Permanent magnets have been used in many applications and industries a long time ago since earlier 20th century. It has been used for consumer electronics, appliances and tools, factories automation and also for medical and educational purposes. Nowadays, peoples are coming with researches to produce permanent magnet with greater strength for heavy applications and also to reduce the volume of the magnet without compromising the magnetic properties. One of its applications is in Permanent Magnet DC Motor (PMDC motor). The author studied the effect of performance of a DC motor by replacing a ferrite magnet with the melt spun NdFeB Magnet. In this project the author fabricated a bonded NdFeB for a DC motor from NdFeB alloy powders which are produced from melt spinning process. The magnet is fabricated by using compression moulding technique and using epoxy as its binder. The fabricated magnet is then magnetised by using magnetizer. Besides, microstructure and chemical properties of the magnet is checked by using optical microscope and also Scanning Electron Microscopy (SEM) with chemical analysis. Magnetic properties of the magnet is also analysed by using Vibrating Sample Magnetometer (VSM). Physical properties of the magnet such as the density is also will be analysed. After all the work done, the DC motor speed increased for 38.3%. This result shows that by replacing ferrite magnet with bonded NdFeB magnet able to build a more efficient motor.